Compensation for abused foreign domestic workers: A problem of enforcement - ONG, Benjamin Joshua (Institutional Knowledge at Singapore Management University, 2020)
In Tay Wee Kiat v Public Prosecutor [2018] 5 SLR 438; [2019] 5 SLR 1033, two offenders who had abused a foreign domestic worker had been ordered to pay her compensation, on pain of a default term of imprisonment. When they failed to pay, the Prosecution applied for the compensation order to be enforced by way of attachment of the offenders’ property or garnishment of debts due to the offenders (“garnishment/attachment orders”). The High Court refused to make garnishment/attachment orders on the grounds that (a) the Prosecution had applied for such orders belatedly; and (b) such orders would lead to “undue protraction” of proceedings. This note argues that the High Court erred in so refusing. Compared to relying on default imprisonment terms as the means of enforcing compensation orders, making garnishment/attachment orders would better comport with the statutory compensation scheme for the High Court, be more economically efficient, and better promote the welfare of abused foreign domestic workers.